USING SHORT STORIES IN ENGLISH TO IMPROVE YOUNG LEARNERS’ SPEAKING SKILLS (Web of Teachers: Inderscience Research, 2024)
This article focuses on how teachers can provide opportunities in the classroom to increase students’ confidence and fluency. It highlights several important aspects to consider when helping students develop their speaking skills, specifically by using short stories in English to enhance young learners’ speaking abilities.